2021
DOI: 10.1111/ppl.13565
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling salt‐responsive tissue‐specific metabolic pathways in olive tree

Abstract: Salinity is a serious constraint that reduces olive crop productivity. Here, we defined metabolite and gene expression changes in various tissues of olive trees (cv. "Chondrolia Chalkidikis") exposed to 75 mM NaCl for 45 days. Results showed that salinity induced foliar symptoms and impaired growth and photosynthetic parameters. The content of Na + and Cl À in roots, xylem, phloem and leaves increased, although the Na + levels in old leaves and Cl À in young leaves remained unaffected. Mannitol was accumulated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 62 publications
2
11
0
Order By: Relevance
“…A major challenge in characterizing plant metabolism under stress is the compartmentalization at the level of cells and organelles. Distinct tissue-specific metabolic responses to abiotic stresses have been characterized in many plant species [ 76 , 216 , 217 ]. In contrast, our knowledge of cell-specific and organelle-specific metabolic responses has been hampered by the limitations of current analytical methods to determine the cellular and subcellular location of metabolites.…”
Section: Challenges and Perspectives In Deciphering Plant Metabolic R...mentioning
confidence: 99%
“…A major challenge in characterizing plant metabolism under stress is the compartmentalization at the level of cells and organelles. Distinct tissue-specific metabolic responses to abiotic stresses have been characterized in many plant species [ 76 , 216 , 217 ]. In contrast, our knowledge of cell-specific and organelle-specific metabolic responses has been hampered by the limitations of current analytical methods to determine the cellular and subcellular location of metabolites.…”
Section: Challenges and Perspectives In Deciphering Plant Metabolic R...mentioning
confidence: 99%
“…Furthermore, a lower malic acid content was observed in the infected samples compared to the non-infected counterparts. Malic acid is a key metabolite in the biosynthesis of amino acids and fatty acids and is involved in the citric acid cycle [59]. In a previous NMR-based metabolomics study, a decrease in malate content was observed in symptomatic Huanglongbing (HLB) leaf extracts [60].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, an 8-fold increase of the first enzyme in this pathway DOXP-synthase is detected, while intermediate synthases exclusive to iridoid synthesis, are only 3.5-and 2-fold. The enhanced activation of DOXP-synthase speaks of an activation devoted to feed synthesis of other relevant terpenes with physiological or biological activity, such as ABA, key for stomatal control, or oleacin synthesis ( El and Karakaya, 2009 ; Li et al, 2020 ; Skodra et al, 2021 ; Xie et al, 2021 ). A striking 5-fold increase in the target metabolite oleuropein was found, suggesting either activation of the final step in the pathway, or a strong inhibition of oleuropein-β-glucosidase (OeGLU), the enzyme that would transform oleuropein into its aglycon, which would be further transformed into oleacin by demethylation and decarboxylation ( Koudounas et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, photosynthesis arrest may happen due to many factors including high light intensity, temperature, and water resource availability ( Skodra et al, 2021 ). On one hand, the usual oxidative stress of light reactions is further enhanced under stress and needs to be counteracted by an active ROS scavenging system, allowing ROS within healthy levels for systemic metabolic coordination ( Baxter et al, 2014 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation